Narrative and Truthfulness through the Body: Interpreting Mark Wynn - David, Edward A. (Studies in Christian ethics, 2022)
This short article responds to, and interprets, two epistemic claims made by Mark Wynn concerning truth and Christian ethics. The first claim concerns how the body knows something prior to an operation of reason. The second claim concerns the relationship between narrative and metaphysics, particularly when considering the eucharist. The article interprets these claims by drawing upon Wynn's previous work in religious epistemology, and it points to its moral and doctrinal relevance for Christian ethicists today.